Chromatographic Separation Studies of Cephalosporins on CTAB Modified Silica Layers with Different Buffer Solvent Systems - Ali, Mohammad; Bhawani, Showkat Ahmad; Sharma, S. (Sai Scientific Communications, 2009)
Various surfactant modified silica layers were used for the chromatography of five different Cephalosporins. The 4% methanolic CTAB impregnated silica layer was useful for the chromatography of Cephalosporins. The acidic buffer solvent systems were used with the 4% methanolic CTAB impregnated silica layers for the separation of different mixtures [A (Cefaclor, Ceftriaxone and Cefadroxil), B (Ceftriaxone, Cefoprazone and Cephalexin) and C (Cefaclor, Ceftriaxone and Cephalexin)] of Cephalosporins. The interference due to the presence of sodium and potassium salts, glucose and urea on the identification and mobility of all the five Cephalosporins were also examined.